Eksplorasi dan Perancangan Prototipe Aplikasi Kantor Maya Untuk Meningkatkan Sustainable Competitive Advantage di Perguruan Tinggi - Yusepaldo Pasharibu; Hari Sunarto; Agus Sugiarto; Yunita Budi Rahayu Silintowe (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
Sustainable competitive advantage for universities could not be separated from the information technology. Actually, some universities have been implemented this information technology, especially virtual office applications. Eventhough, the virtual office applications were implemented, but preliminary research found that those applications used were Online Transaction Processing only, not Online Analytical Processing that can be used to make decision. Based on those explanations, this research had been done to explore and design the virtual office prototype application for universities. Three methods were used to conduct this reseach, which were explorative, validation, and application design. Finally, prototype applications of virtual office dashboard, lecturer dashboard and accreditation dashboard to improve sustainable competitive advantage for universities were presented as this study result.